2015
DOI: 10.1155/2015/674641
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms during an Acute Schizophrenic Episode: Frequency and Clinical Correlates

Abstract: Introduction. Depressive symptoms are common in schizophrenia and are associated with poorer functioning, lower quality of life, and an elevated risk of suicidal behaviour. There are few studies on the occurrence and correlates of these symptoms in acutely ill patients with schizophrenia. Method. 72 acutely ill patients with schizophrenia were assessed for depression using the Calgary Depression Scale for Schizophrenia (CDSS). A cut-off score of ≥6 on the CDSS was used to identify clinically significant depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…This study suggests that demographic variables like age, gender, education, marital status, occupation, religion, locality, type of family and income of patient/family do not have any significant influence on the presence or absence of depression. This finding supports the earlier studies which have also in general reported lack of influence of these variables on depression among patients with schizophrenia (Majadas et al, 2012; Rajkumar, 2015); however, few studies suggest that depression in schizophrenia is associated with increasing age (Ampalam et al, 2012; Tharyan & Kuruvilla, 1994). Findings of this study do not support the same.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study suggests that demographic variables like age, gender, education, marital status, occupation, religion, locality, type of family and income of patient/family do not have any significant influence on the presence or absence of depression. This finding supports the earlier studies which have also in general reported lack of influence of these variables on depression among patients with schizophrenia (Majadas et al, 2012; Rajkumar, 2015); however, few studies suggest that depression in schizophrenia is associated with increasing age (Ampalam et al, 2012; Tharyan & Kuruvilla, 1994). Findings of this study do not support the same.…”
Section: Discussionsupporting
confidence: 90%
“…Very few studies have evaluated the correlates of depression in patients with schizophrenia. In general, data suggest that the depression in schizophrenia is not associated with sociodemographic variables (Majadas, Olivares, Galan, & Diez, 2012; Rajkumar, 2015); however, few Indian studies suggest that depression in schizophrenia is associated with increasing age (Ampalam, Deepthi, & Vadaparty, 2012; Tharyan & Kuruvilla, 1994). In terms of clinical variables, most of the studies have found no association of depressive symptoms with duration of illness (DOI), positive and negative symptom scores and extrapyramidal side effects (Baynes et al, 2000; Bottlender et al, 2000; Fervaha, Foussias, Agid, & Remington, 2014; Goldman, Tandon, Liberzon, & Greden, 1992; Mauri et al, 1999; Owens & Johnstone, 1989; Siris & Bench, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Depressive symptoms are also broadly associated with early childhood adversities (Mandelli, Petrelli, & Serretti, 2015) and commonly found in schizophrenia spectrum disorders on every phase of illness (Rajkumar, 2015) including the prodromal/pre-psychotic one (Myles-Worsley, Weaver, & Blailes, 2007), but their effect on risk of transition-to-frank psychosis is not proven (Fusar-Poli, Nelson, Valmaggia, Yung, & McGuire, 2014).…”
mentioning
confidence: 99%
“…The socio-demographic profile of the patients in this study was similar to other studies. 15,21,22 Majority of the patients were on at least one atypical antipsychotic which may be indicative of the higher prescription rates of atypical antipsychotics that have been observed through the years. 23 Historically, it has been stated that the presence of mood symptoms in schizophrenia may be a good prognostic indicator, with patients who have high levels of affective symptoms appearing more on the "bipolar" rather than the deficit end of a psychosis continuum model.…”
Section: Discussionmentioning
confidence: 99%